2017
DOI: 10.3389/fpls.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Submergence-Responsive MicroRNAs and Their Targets Reveals Complex MiRNA-Mediated Regulatory Networks in Lotus (Nelumbo nucifera Gaertn)

Abstract: MicroRNAs (miRNAs) are endogenous non-coding RNAs with important regulatory functions in plant development and stress responses. However, their population abundance in lotus (Nelumbo nucifera Gaertn) has so far been poorly described, particularly in response to stresses. In this work, submergence-related miRNAs and their target genes were systematically identified, compared, and validated at the transcriptome-wide level using high-throughput sequencing data of small RNA, Mrna, and the degradome. A total of 128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 86 publications
(103 reference statements)
3
35
0
2
Order By: Relevance
“…For instance, gene expression profiling and qRT-PCR analyses revealed the varied expression patterns of miR169u and miR396a-3p in A. philoxeroides during submergence. The similar patterns were also found in Nelumbo nucifera ( Jin et al, 2017 ) and Zea mays ( Zhang et al, 2008 ; Liu et al, 2012 ). Three members of the miR167_1 family (miR167b-3p, miR167d-5p, and miR167d-3p) showed significantly altered expression between the pond- and upland-treated samples in A. philoxeroides .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For instance, gene expression profiling and qRT-PCR analyses revealed the varied expression patterns of miR169u and miR396a-3p in A. philoxeroides during submergence. The similar patterns were also found in Nelumbo nucifera ( Jin et al, 2017 ) and Zea mays ( Zhang et al, 2008 ; Liu et al, 2012 ). Three members of the miR167_1 family (miR167b-3p, miR167d-5p, and miR167d-3p) showed significantly altered expression between the pond- and upland-treated samples in A. philoxeroides .…”
Section: Discussionsupporting
confidence: 76%
“… Ren et al (2012) found significant changes in the expression of seven conserved microRNA families and five novel microRNAs in response to flooding stress in Populus tomentosa . Jin et al (2017) revealed the microRNA-mediated regulatory networks in lotus by identifying submergence-responsive microRNAs and their targets. Flooding exposes plants to severe hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small RNA molecules with pivotal roles in the response to environmental stresses in plants that usually act as negative regulators of gene expression via silencing target genes, which are recognized by sequence complementarity and subsequently targeted for degradation and/or translation inhibition [ 22 ]. With the development of new platforms for the high-throughput sequencing of small RNAs, several miRNAs involved in the response to drought or submergence have been described in plants such as Arabidopsis thaliana [ 23 , 24 ], Brachypodium distachyon [ 25 , 26 ], Oryza sativa [ 27 ], Nelumbo nucifera , [ 28 ] and Zea mays [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Utrzymanie odpowiedniego poziomu energii w takich warunkach jest możliwe, między innym, dzięki zahamowaniu syntezy skrobi i indukcji jej rozkładu. W przypadku siewek L. japonicus oraz kukurydzy, zatopienie powoduje zmniejszenie poziomu miR399, co skutkuje zwiększeniem ilości ich docelowego mRNA kodującego β-amylazę [46]. U kukurydzy wykazano także obniżenie poziomu miR159, miR395, miR474 i wzrost ich przewidywanych docelowych mRNA tj.…”
Section: Analiza Transkryptomu Roślin Poddanych Niedotlenieniuunclassified
“…W przypadku siewek L. japonicus miR319 zmniejsza poziom genu TCP4 (ang. TEO-SINTE BRANCHED/CYCLOIDEA/PROLIFERATING CELL FACTORS), którego produkt jest jednym z negatywnych regulatorów cyklu komórkowego i ma kluczowe znaczenie dla wzrostu i rozwoju płatków [46]. Wykazano także wzrost ilości miR156, który kontroluje ekspresję mRNA czynników transkrypcyjnych SPL (ang.…”
Section: Analiza Transkryptomu Roślin Poddanych Niedotlenieniuunclassified